Perancangan Pembangkit Listrik Tenaga Surya (PLTS) Sistem On-Grid Berbasis Homer Untuk Memenuhi Energi Listrik Di Sekolah Menengah Pertama Negeri (SMPN) 1 Teriak, Bengkayang Kalimantan Barat - Jenni Lisdawati; Silalahi, Eva Magdalena; Purba, Robinson (Prodi Teknik Elektro FT UKI, 2022)
PLTS designed in the SMPN 1 Teriak building, Bengkayang, West Kalimantan with a power of 6600 W, is an on-grid PLTS with the aim of reducing electricity bills. In this design and analysis of the design results, both from the technical and economic sides, the Homer application is used. Based on the analysis of the design, the results were obtained, namely, the capacity of the On-Grid PLTS system is 0.250 kW / module with the number of Photovoltaic (PV) modules 27 units and 3 inverter units, the total cost of the two components is Rp. 130,397,740. The need for electrical power per day is 14,500 Wh or 14.5 kWh. The On-Grid solar system produces electrical energy of 9,969 kWh per year (65.5%), while the electrical energy produced by the Grid reaches 5,254 kWh / day (34.5%) with a total electrical energy production of 15,223 kWh per year (100%). Homer's simulation results also showed that the Net Present Cost (NPC) value of the PLTS+Grid system was Rp.36,064,610 and the Levelized Cost of Electricity (LCOE) value of the PLTS+Grid system was Rp.189.47/kWh lower than the LCOE value of the Grid system. And the length of payback for the Break Event Point (BEP) PLTS+Grid system is 5.36 years.